Pension reform in Central and Eastern Europe : necessity, approaches and open questions - Holzmann, Robert (UN ECLAC SantiagoCL, 1997)
Reviews the need for reform, surveys the reform discussion and presents a summary of current reform plans in individual countries. Addresses three central but open questions of the reform approach viz. how to structure the first and unfunded tier?, how to finance the transition toward the second and funded tier?, and what are the minimum financial sector requirements before funded provisions can be initiated.